Effect of Cephalothin and Ambien Clox and their respective accompaniment with dnaell in the level of glucose and cholesterol in healthy rats and experimental diabetes - Ismaeel Mohammed; Motaa Abd; Hamed Abdullah (College of Education for Pure Sciences, 2007)
ABSTACT Cephalothin & ampiclox were chosen and drug used in diabetic case (daonil), to know the effect of them alone and in combination with daonil on glucose and cholesterol levels in healthy and diabetic case. Some of rats were injected with alloxan (100 mg / kg body weight) to be diabetic and others left without injection to remain as control rats. In this research cephalothin was used 50 mg / kg body weight intramuscular once daily and lasted for 5 successive days, ampiclox was used 25 mg / kg body weight intramusculary once daily & lasted for 5 successive days & daonil was used 1 mg / kg body weight. Daonil showed reduction in the level of serum glucose in control rats, also in combination with cephalothin or ampiclox, but the combination do not increased the reduction effect of daonil, also single treatment of them did not significantly affect glucose level in these rats. Combination between cephalothin and daonil and combination between ampiclox and daonil showed reduction in glucose level in the diabetic rats, neither all of the single treatment did not show any significant effect on glucose level of diabetic rats, which mean that combination caused this reduction effect. Single treatment of daonil, ampiclox, combination between them and combination between daonil with cephalothine showed reduction in cholesterol level in diabetic rats. This study confirmed that the two antibiotics cephalothin and ampiclox have the ability to potentiate daonil blood glucose reduction effect in diabetic case and ampiclox alone and daonil alone both of them have reduction effect on blood cholesterol level in diabetic rats.